Letramento visual na multimodalidade, a educação para o olhar ético e estético das crianças que fotografam e publicam - Tatiane Nunes de Souza (2021)
This research aimed to investigate a progression in the development of visual literacy from the perspective of an education for the eye, in the possibility of making the digital multimodal space of texts through activities with photographs captured by children at school. This educational environment made use of texts with multimodal language on supports, in limited situations, in a scenario where children have easy access to different imagery situations, in order to create, consume and share multimodal content, in digital format. The General Objective of this investigation was analyzed as the children read, appreciate and rely on non-verbal texts to develop an ethical and aesthetic look through different hypotheses of reading and the creation of digital images from photography. Thus, the research question asked: how to develop an ethical and aesthetic education, from the perspective of children from 6 to 8 years old, students from public schools, through the production of photographs and narratives published on the internet? It intended to answer these questions by highlighting the possibility of critical, ethical and citizen human training by placing the child in the position of producer, of the photographs, by expanding the required skills, including in the guidelines of the Base Nacional Comum Curricular, in addition to having the collaboration of children in preparation of a manual for children to photograph. The entire methodological path aimed to develop activities in analogue and digital media as opposed to school actions that recommend writing and reading restricted on paper, as the predominant source to guarantee literacies. In order to analyze and reflect on the imagery dimension with children, this research was defined from a qualitative methodological approach based on a case study and for data collection, observation, focus group and inquiry were adopted. Theoretical support is based on authors who developed their studies around technology such as Harari (2016), Kenski (2012), Lévy (2010, 2011), others who address the topic of literacy(s) like Ribeiro (2012), Rojo and Moura (2012), Coscarelli (2016), and also in relation to multimodality Kress (1996-2010) and Van Leeuwen (2003). In the specific case of studies related to image, studies by Barbosa (1998), Santaella (2012) and Dondis (2011) were used, the latter also in the field of photography. What was expected as a result were that children expand multimodal reading and writing skills, with a view to developing, for example, visual literacy, especially with a view to consumption and that promotes a manual that meets the needs of its target audience based on studies by Gestalt (Filho, 2008), with the purpose of allowing other children or educators, to rely on him to multiply the proposal that was developed in this work.